Haplotype Association of the MAP2K5 Gene with Antipsychotics-Induced Symptoms of Restless Legs Syndrome among Patients with Schizophrenia - Kang, Seung-Gul (Psychiatry Investig, 2018)
OBJECTIVE: Restless legs syndrome (RLS) is considered a genetic disease and, following a genome-wide association study conducted in 2007, the mitogen-activated protein kinase 5 (MAP2K5) gene has been regarded as the promising candidate gene for RLS. The present study investigated whether polymorphisms of MAP2K5 are associated with antipsychotics-induced RLS in schizophrenia. METHODS: We assessed antipsychotics-induced RLS symptoms in 190 Korean schizophrenic patients using the diagnostic criteria of the International Restless Legs Syndrome Study Group. Five single-nucleotide polymorphisms (SNPs) of MAP2K5 were genotyped. We investigated genetic and haplotypic associations of these five SNPs with the risk of antipsychotics-induced RLS symptoms. RESULTS: We divided the 190 subjects into 2 groups: 1) those with RLS symptoms (n=96) and 2) those without RLS symptoms (n=94). There were no significant intergroup differences in the distributions of the genotypes and alleles of the rs1026732, rs11635424, rs12593813, rs4489954, and rs3784709 SNPs. However, the haplotype analysis showed that the G-G-G-G-T (rs1026732-rs11635424-rs12593813-rs4489954-rs3784709) haplotype was associated with RLS symptoms (permutation p=0.033). CONCLUSION: These data suggest that a haplotype of MAP2K5 polymorphisms confers increased susceptibility to antipsychotics-induced RLS symptoms in schizophrenic patients.